2008
DOI: 10.1136/jnnp.2007.126565
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injury does not predict acute postconcussion syndrome

Abstract: There is a high rate of acute PCS in both mTBI and non-brain injured trauma patients. PCS was not found to be specific to mTBI. The use of the term PCS may be misleading as it incorrectly suggests that the basis of PCS is a brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(214 citation statements)
references
References 32 publications
9
202
1
2
Order By: Relevance
“…Historically, Veterans returning from war have reported cognitive complaints, which, in the vast majority of cases, are not attributable to TBI [26][27]. Cognitive postconcussive symptoms often lack objective neurocognitive findings, and studies in civilians have shown that these symptoms occur at similar rates in persons with mTBI as in those with no TBI [28][29]. More recently, Polusny et al showed that deployment-related mTBI was significantly associated with two self-reported cognitive outcomes (memory and concentration problems) among National Guard servicemembers deployed to Iraq [30].…”
Section: Memory and Attentionmentioning
confidence: 99%
“…Historically, Veterans returning from war have reported cognitive complaints, which, in the vast majority of cases, are not attributable to TBI [26][27]. Cognitive postconcussive symptoms often lack objective neurocognitive findings, and studies in civilians have shown that these symptoms occur at similar rates in persons with mTBI as in those with no TBI [28][29]. More recently, Polusny et al showed that deployment-related mTBI was significantly associated with two self-reported cognitive outcomes (memory and concentration problems) among National Guard servicemembers deployed to Iraq [30].…”
Section: Memory and Attentionmentioning
confidence: 99%
“…Other authors have reported similar findings. 9,23,55,56 Meares et al 9 studied a sample of consecutive trauma patients admitted to a level 1 trauma center, including 90 patients with mild TBI and 85 with non-brain injury trauma: both groups had the same incidence of symptoms, with the strongest predictor of symptoms in either group being a previous affective disorder. A correlation between pain and NBS has been reported, and pain has been associated with the persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between pain and NBS has been reported, and pain has been associated with the persistence of symptoms. 9,56 Hart et al 56 reported that pain after TBI was associated with cognitive impairment, including deficits in attention, memory, processing speed, and reaction time. The occurrence of cognitive complaints in non-TBI chronic pain patients has been demonstrated, and this once again questions the relationship between TBI per se and NBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery after mTBI usually occurs within a period of days to weeks [2,4]; however, a sizable minority (18%-30%) of individuals in certain samples continues to report persistent postconcussive complaints, such as headache, light sensitivity, depressed mood, and reduced attention, many months to years after injury [5][6][7]. Persistent postconcussive symptoms are associated with poor functional outcomes [8][9][10], such as difficulty returning to work or school. Pain [11], secondary gain [12], and psychiatric comorbidities, such as posttraumatic stress disorder (PTSD) and depression, notably contribute to poor prognoses [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%